Purification and properties of an alkaline protease of Aspergillus clavatus - Tremacoldi, C. R.; Monti, Rubens [UNESP]; Selistre-De-Araujo, H. S.; Carmona, E. C. (Springer, 2007)
An extracellular alkaline serine protease has been purified from a strain of Aspergillus clavatus, to apparent homogeneity, by ammonium sulfate precipitation and chromatography on Sephadex G-75. Its molar mass, estimated by SDS-PAGE, was 35 kDa. Maximum protease activity was observed at pH 9.5 and 40 degrees C. The enzyme was active between pH 6.0 and 11.0 and was found to be unstable up to 50 degrees C. Calcium at 5 mM increased its thermal stability. The protease was strongly inhibited by PMSF and chymostatin as well as by SDS, Tween 80 and carbonate ion. Substrate specificity was observed with N-p-Tos-Gly-Pro-Arg-p-nitroanilide and N-Suc-Ala-Ala-Ala-p-nitroanilide being active substates. Parts of the amino acid sequence were up to 81% homologous with those of several fungal alkaline serine proteases.
Keywords: alkaline protease; Aspergillus clavatus; characterization; enzyme purification; sequence